Legal and Ethical Considerations in the Use of Force against Civilian Aircraft - Török, Csaba (Faculty of Law Universitas Lampung, 2024)
Using weapons against civilian aircraft intersects with several critical areas: international legal responsibility, the prohibition of force, the right to self-defense, ethical dilemmas, and the protection of human rights. The arguments presented in this paper emphasize that while self-defense may theoretically allow for the use of weapons against aircraft, there are substantial ethical challenges and strict international legal norms that cannot be ignored. Therefore, employing weapons against civilian aircraft poses numerous challenges that necessitate thorough consideration of both legal and moral aspects. This paper discusses the international legal liability regime for using weapons against civilian aircraft, as well as the associated human rights and ethical responsibilities.